The effect of l-citrulline and watermelon juice supplementation on anaerobic and aerobic exercise performance - Cutrufello, P. T.; Gadomski, S. J.; Zavorsky, G. S. (Journal of Sports Sciences, 2015)
Citrulline has been proposed as an ergogenic aid, leading to an interest in watermelon given its high citrulline concentration. The aim of this study was to determine the effects of a single, pre-exercise dose of l-citrulline, watermelon juice, or a placebo on the total maximum number of repetitions completed over 5 sets, time to exhaustion, maximal oxygen consumption (VO2max), anaerobic threshold, and flow-mediated vasodilation. A randomised double-blind within-participants study design was used to examine these effects among 22 participants (n = 11 males). Supplementation included either a 7.5% sucrose drink containing 6 g of l-citrulline, 710 mL of watermelon juice (~1.0 g citrulline), or a 7.5% sucrose placebo drink. Supplementation was administered 1 or 2 h before exercise testing to investigate a timing effect. There was no significant effect between the three supplements for the total number of repetitions, time to exhaustion, VO2max, anaerobic threshold, or flow-mediated vasodilation. There was also no interaction observed relative to gender or supplement timing (P > 0.05). A single dose of l-citrulline or watermelon juice as a pre-exercise supplement appears to be ineffective in improving exercise performance; however, greater doses of l-citrulline have been shown to be safe and are currently left unexamined.